Preparation of Zn Nanosystems and Some Peculiarities of Their Oxidation - V.M. Latyshev; A.S. Kornyushchenko; V.I. Perekrestov (Журнал нано- та електронної фізики)
The peculiarities of the zinc nanosystem formation by means of the low saturated vapor condensation in the high-clean inert medium with the variation of technological parameters, such as the magnetron sputtering discharge power and the plasma-forming gas pressure (Ar) have been studied. By means of the XRD- and the SEM-studies it is determined that the most thin and interconnected zinc nanowires are generated under the plasma-forming gas pressure of 12 Pa and the magnetron sputtering discharge power of 30 W. It is shown that the zinc nanosystem oxidation processes with the most possible preservation of the morphology of the initial structures are possible due to the use of CO2 and O2 gas mixture as an oxidizing medium.